2019
DOI: 10.1186/s12870-019-1878-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis reveals important roles of nonadditive genes in maize hybrid An’nong 591 under heat stress

Abstract: Background Heterosis is the superior performance of F 1 hybrids relative to their parental lines for a wide range of traits. In this study, expression profiling and heterosis associated genes were analyzed by RNA sequencing (RNA-Seq) in seedlings of the maize hybrid An’nong 591 and its parental lines under control and heat stress conditions. Results Through performing nine pairwise comparisons, the maximum number of differentially expressed ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 57 publications
10
52
0
Order By: Relevance
“…For example, 3 genes were found to be involved in the spliceosome pathway. Consistent with many studies, our previous study indicated that heat stress can result in a signi cant increase in the number of alternative splicing (AS) events [32], which can be regulated by different plant developmental stages and environmental stress [55,56]. In addition, one gene was targeted by a DEM (zma-miR169i-3p_R + 1_1) with down-regulated expression, and involved in the mitogen-activated protein kinase (MAPK) signaling pathway that has been demonstrated to play important roles in plant growth and development, and stress response [57].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…For example, 3 genes were found to be involved in the spliceosome pathway. Consistent with many studies, our previous study indicated that heat stress can result in a signi cant increase in the number of alternative splicing (AS) events [32], which can be regulated by different plant developmental stages and environmental stress [55,56]. In addition, one gene was targeted by a DEM (zma-miR169i-3p_R + 1_1) with down-regulated expression, and involved in the mitogen-activated protein kinase (MAPK) signaling pathway that has been demonstrated to play important roles in plant growth and development, and stress response [57].…”
Section: Discussionsupporting
confidence: 85%
“…In our previously study [32], we reported that maize inbred line CM1 exhibits high tolerance to high temperature stress. To identify miRNAs involved in the response to heat stress, six small RNA libraries were constructed from the leaves of maize inbred line CM1 under heat treatment (MH1, MH2 and MH3) and normal conditions (MC1, MC2 and MC3).…”
Section: High-throughput Sequencing and Data Analysis Of Small Rnasmentioning
confidence: 91%
See 1 more Smart Citation
“…Most of the methods detecting variation are based on sequencing data derived either from whole-genome sequencing (WGS) or whole-exome sequencing (WES) [ 10 , 11 ]. In the last few years, NGS approaches in the form of RNA-seq have been co-opted to provide global insights into the gene expression patterns to understand the genetic networks and metabolic pathways involved in maize responses to heat stress [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Apart from gene expression analysis, RNA-seq can also be used to identify genomic variants in expressed genes alongside WGS and WES [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In past years, many transcriptome studies have provided insights into the molecular basis of heterosis in different species like rice [8,12], Arabidopsis [13,14] and maize [15,16]. In these studies, a vast number of DEGs associated with different biochemical pathways have been found related to heterosis.…”
Section: Introductionmentioning
confidence: 99%